IMPLEMENTASI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IIIB SD MUHAMMADIYAH 6 PEKANBARU - Dara Primalisa; Gustimal Witri; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the low of outcomes in mathematics learning of grade IIIB students in Muhammadiyah 6 Elementary School in Pekanbaru, which is have an average grade of 57.Meanwhile the completeness criteria minimum value (KKM) in Mathematic subject is 73. From 20 students, there are only 5 students who achieve the KKMwith classical completeness of 25%. This research is the type of Classroom Action Research (CAR) which the aims is to improve outcomes inMathematics learning of student grade IIIB students in Muhammadiyah 6 Elementary School in Pekanbaruby implementing Pendidikan Matematika Realistik Indonesia (PMRI) approach.The data which are collected in this research are the teachers and students activity observation sheets and also the learning report. The results obtained by studying the average learning outcome measures 57 rising to 68,9 in cycle I with rising percentage 20,88%. In cycle ricing to 80,75 with rising percentage 41,67%. Teacher activity in the cycle I of the first meeting obtained score of 13 (65%) with sufficient category and at the second meeting obtained score of 14 (70%) with sufficient category. While on the cycle II of the first meeting obtained the score of 16 (80%) with good category and the second meeting obtained score of 18 (90%) with very good category. The increasing of student activity on cycle I of first meeting get score of 15 (62,5%) with enough category and at second meeting get the score of 16 (65%) with enough category. While in the cycle II of the first meeting obtained score of 19 (79.17%) with good category and the second meeting obtained a score of 20 (83.3%) with good category. The result of the research in grade IIIB students in Muhammadiyah 6 Elementary School in Pekanbaru proves that by implementing Pendidikan Matematika Realistik Indonesia (PMRI) approach can improve students' mathematics learning outcomes.Key Word: Pendidikan Matematika Realistik Indonesia (PMRI) approach, Mathematic Learning Outcome